2016
DOI: 10.1111/jre.12353
|View full text |Cite
|
Sign up to set email alerts
|

Salivary pathogen and serum antibody to assess the progression of chronic periodontitis: a 24‐mo prospective multicenter cohort study

Abstract: It is suggested that the combination of P. gingivalis ratio in saliva and serum IgG titers against P. gingivalis may be associated with the progression of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 42 publications
0
29
1
Order By: Relevance
“…The presence of specific antibod ies for oral bacteria in patients with periodontitis indicates an involvement of adaptive immune responses [68], of which different T-cell subsets play a detrimental role in the pathogenesis of this inflammatory disease. The T-cell-associated cytokine profile in gingival tissue suggests an engagement of T-helper (Th) 1, Th2, and Th17 cells [69][70][71].…”
Section: Leukocytesmentioning
confidence: 99%
“…The presence of specific antibod ies for oral bacteria in patients with periodontitis indicates an involvement of adaptive immune responses [68], of which different T-cell subsets play a detrimental role in the pathogenesis of this inflammatory disease. The T-cell-associated cytokine profile in gingival tissue suggests an engagement of T-helper (Th) 1, Th2, and Th17 cells [69][70][71].…”
Section: Leukocytesmentioning
confidence: 99%
“…Each sample thus collected was centrifuged at 3,000 rpm for 5 min at 4ºC. All the samples were collected in the order described above and then immediately sent to a medical examination laboratory (BML Corporation, Tokyo, Japan) for bacterial analysis (7)(8)(9)12).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Briefly, bacterial DNA was extracted using a commercial kit (MagNA Pure LC Total Nucleic Acid Isolation Kit, Roche, Basel, Switzerland). Primary probes and Invader oligos were used as described previously (7,12). Each tube contained 15 μL of reaction mixture containing 50 μM dNTP, 700 nM primary probe, 70 nM Invader oligo, 2.5 U polymerase chain reaction (PCR) enzyme (EagleTaq DNA polymerase, Roche), and the Invader core reagent kit (Cleavase XI Invader core reagent kit, HOLOGIC, Marlborough, MA, USA) containing a fluorescence resonance energy transfer (FRET) mix, an enzyme/MgCl 2 solution and template DNA.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that these pathogens would be able to mediate the microbial community’s conversion into dysbiosis, and a wide perturbation of this community would cause and/or sustain the process of periodontal breakdown 20 . In a recent multicenter clinical study in Japan, it was suggested that the combination of Pg ratio in saliva and serum immunoglobulin G (IgG) titers against Pg may be associated with progression of periodontitis 21 . Imamura et al 22 previously reported on a novel immunochromatographic device (DK13‐PG‐001) for rapid and accurate clinical detection of Pg in subgingival plaque.…”
mentioning
confidence: 99%